Genomics in Asia a clash of bioethical interests? - Sleeboom-Faulkner, Margaret 1961-. (London New York Kegan Paul, 2004)
"This book provides insights into the social, political and ethical aspects of genomics, and reflects the bioethical experiences of researchers from Japan, China, the Filippines, Thailand, Taiwan, Pakistan, India and Malaysia. Topics of discussion range from genetics in China to religious perspectives on cloning and genetic therapy."--BOOK JACKET.
Selected conference papers.
Includes bibliographical references.
Keywords: Genomics -- Asia -- Congresses; Genomics -- Moral and ethical aspects -- Congresses